Heat shock proteins in prostate cancer: From tumorigenesis to the clinic - Ciocca, Daniel Ramon (2010)
The heat shock proteins (HSP) constitute a superfamily of chaperone proteins present in all cells and in all cell compartments, operating in a complex interplay with synergistic/overlapping multiplicity of functions, even though the common effect is cell protection. Several reasons explain the need for investigating HSP in prostate cancer: (1) these molecules function as chaperones of tumorigenesis accompanying the emergence of prostate cancer cells, (2) they appear as useful molecular markers associated with disease aggressiveness and with resistance to anticancer therapies including hormone therapy, radiotherapy, chemotherapy and hyperthermia, and (3) they can be used as targets for therapies. The latter can be accomplished by: (i) interrupting the interaction of HSP (mainly HSPC1) with various client proteins that are protected from degradation when chaperoned by the HSP; (ii) using the chaperone and adjuvant capabilities of certain HSP to present antigenic peptides to the immune system, so this system can recognise the prostate tumour cells as foreign to mount an effective antitumoral response; and (iii) using treatment planning models taking into account the HSP expression levels to obtain more effective therapies. In summary, the study of the HSP during tumorigenesis as well as during cancer progression, and the inclusion of treatment designs targeting HSP combined with other treatment modalities, should improve prostate cancer survival in the near future.